IMPACT OF DIGITAL MARKETING ADOPTION ON ORGANIZATION PERFORMANCE AND CORPORATE REPUTATION: ROLE OF OPEN INNOVATION CLIMATE IN IT ENABLED SECTOR IN DELHI NCR - Hunasgi, Raghavendra Pranesh (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The current study's goal is to find out how open innovation environments in businesses affect the adoption of digital marketing, which is a requirement for improving business reputation and organizational performance. According to a recent report by The Economist Group titled "The Open Innovation Barometer," more than 90% of organizations have either adopted or intend to implement open innovation practices in the next three years, including allowing cross-organizational collaboration on innovation. This is the reason a more thorough understanding of the situation is required. Companies can evaluate their prospects for growth by knowing how performance and brand image are impacted by open innovation and digital marketing efficacy. The study sets the stage for an empirical investigation of the suggested relationships by putting forth a theoretical framework. This investigation can yield further insightful information that can guide strategic decision-making and create an atmosphere that is more favorable for open innovation practices within the designated organizational context.